2012
DOI: 10.1016/s0140-6736(12)60898-8
|View full text |Cite
|
Sign up to set email alerts
|

The pandemic of physical inactivity: global action for public health

Abstract: Physical inactivity is the fourth leading cause of death worldwide. We summarise present global efforts to counteract this problem and point the way forward to address the pandemic of physical inactivity. Although evidence for the benefits of physical activity for health has been available since the 1950s, promotion to improve the health of populations has lagged in relation to the available evidence and has only recently developed an identifiable infrastructure, including efforts in planning, policy, leadersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
1,615
6
162

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,370 publications
(1,810 citation statements)
references
References 43 publications
27
1,615
6
162
Order By: Relevance
“…Indeed, there is a sense in which lay people offer us a novel vision of agency, by pointing to the network of things and issues that impinge on PA. As such, our data undoubtedly give empirical support to those who argue that PA policy must focus on, "populations and the complex interactions among the correlates of physical inactivity, rather than solely a behavioural science approach focusing on individuals" (Kohl, Craig, Lambert et al, 2012).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Indeed, there is a sense in which lay people offer us a novel vision of agency, by pointing to the network of things and issues that impinge on PA. As such, our data undoubtedly give empirical support to those who argue that PA policy must focus on, "populations and the complex interactions among the correlates of physical inactivity, rather than solely a behavioural science approach focusing on individuals" (Kohl, Craig, Lambert et al, 2012).…”
Section: Discussionsupporting
confidence: 53%
“…By 2009 physical inactivity was being described as one of the "most important public health problems of the 21 st century" (Blair, 2009) and more recently as a 'pandemic' (Kohl, Craig, Lambert et al, 2012). The Global Burden of Disease Study (Lim, Flaxman, Danaei et al, 2012) concluded that physical inactivity ranked as the fifth leading cause of disease burden in Western Europe, and as one of the most important of modifiable risk factors; Kohl, Craig, Lambert et al (2012) and the WHO (2010:7) ranked inactivity as the fourth leading cause of death worldwide.…”
Section: And I Know It's Not Your (Ie the Moderator's) Remit But Imentioning
confidence: 99%
“…The mere existence of national physical activity policies or action plans does not ensure their functionality or implementation. Physical activity guidelines are not implementation and implementation does not guarantee change [29]. We can no longer opine that governments, schools, employers, facility managers, urban planners, ministries of education, global organizations, health care professionals, universities, recreation and health departments, community organizations, sport federations, the health care system, and transportation departments, ''should'' do something [8].…”
Section: The Problemmentioning
confidence: 99%
“…Given the impact of unhealthy lifestyles on the chronic disease pandemic [5,16,29] governments began, decades ago, to emphasize lifestyle and behaviour changes to broaden the scope of national health policies beyond traditional medical and surgical interventions [38][39][40]. For this reason, a primary focus on behavioural change as the core component of all clinical programs for the prevention and management of chronic disease is essential.…”
Section: Behavioural Changementioning
confidence: 99%
“…Deconditioning in astronauts after spaceflight is a useful model for studying interventions for optimal recovery, as changes occur relatively rapidly and without the complication of underlying pathology seen in musculoskeletal and neurological disorders, where the effects of disuse are difficult to study in isolation. Physical inactivity is a major problem in the general population, despite well-known benefits, causing a public health concern worldwide (Kohl et al 2012;Lee et al 2012), so translating motivation strategies from astronauts would be very beneficial. Clinical conditions associated with disuse can also provide lessons for optimising exercise programmes to minimise deconditioning during spaceflight and reconditioning the astronaut on their return to Earth.…”
Section: Introductionmentioning
confidence: 99%